Travel agencies in Łódź at the beginning of the 21st century: their origins, types and distribution - Latosińska, Jolanta (Turyzm/Tourism, 2015)
The article presents a continuation of research on the distribution of travel agencies in Łódź, carried out in the mid-1990s, 2006 and 2010 by academics from the Institute of Urban and Tourism Geography. Observations on Łódź travel agencies over the last 25 years lead to the conclusion that it is a dynamic phenomenon. Agencies appear and disappear, change their names and locations, as well as their aims and range of activity. The paper presents a short historical outline of travel agency development in Łódź, a classification of agencies based on aims and range of activity, as well as their distribution within city space. The conclusions concern certain limitations and threats to the further development of Łódź travel agencies resulting from external (formal) and internal causes.